2011
DOI: 10.1029/2011gc003627
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of an extensional shear zone in the mantle, Lanzo massif, Italy

Abstract: [1] Analysis of the microstructures in the km-scale mantle shear zone that separates the northern and the central parts of the Lanzo peridotite massif provides evidence of an evolution in time and space of deformation processes accommodating shearing in the shallow mantle within an extensional setting. This shear zone displays an asymmetric distribution of deformation facies. From south to north, gradual reorientation of the foliation of coarse porphyroclastic plagioclase-bearing peridotites is followed by dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 63 publications
8
56
0
Order By: Relevance
“…Rather than solid-state amphibole deformation, this correlation likely records amphibole crystallization with an orientation that mimics the preexisting, strain-induced CPO of clinopyroxene. Such epitaxial relationship between amphibole and clinopyroxene has been observed by Kaczmarek and Tommasi (2011) in the Lanzo orogenic peridotite (Italy), for instance. It is consistent with microstructural observations suggesting that amphibole crystallized belatedly, compared with secondary clinopyroxene.…”
Section: Linking Deformation Metasomatism and Annealingmentioning
confidence: 92%
“…Rather than solid-state amphibole deformation, this correlation likely records amphibole crystallization with an orientation that mimics the preexisting, strain-induced CPO of clinopyroxene. Such epitaxial relationship between amphibole and clinopyroxene has been observed by Kaczmarek and Tommasi (2011) in the Lanzo orogenic peridotite (Italy), for instance. It is consistent with microstructural observations suggesting that amphibole crystallized belatedly, compared with secondary clinopyroxene.…”
Section: Linking Deformation Metasomatism and Annealingmentioning
confidence: 92%
“…Mt Avic, Aosta Valley, and Breithorn, Zermatt-Saas area, in the Northwestern Alps (Dal Piaz, 1969;Fontana et al, 2008); 3. Lanzo, to the south of the Sesia-Lanzo HP terrane in the Southwestern Alps (Bodinier, 1988;Bodinier et al, 1986Bodinier et al, , 1991Boudier and Nicolas, 1972;Ernst, 1978;Kaczmarek and Mü ntener, 2005, 2008, 2010Kaczmarek and Tommasi, 2011;Mü ntener et al, 2005;Nicolas, 1969;Piccardo et al, 2004bPiccardo et al, , 2005Piccardo et al, , 2007aPognante et al, 1985); 4. Erro-Tobbio in the Voltri group, western Liguria (Bezzi and Piccardo, 1971;Borghini et al, 2007;Chiesa et al, 1975;Hoogerduijn-Strating et al, 1990;Messiga and Piccardo, 1974;Piccardo and Vissers, 2007;Piccardo et al, 1980Piccardo et al, , 1988aRampone and Borghini, 2008;Rampone et al, 2005;Vissers et al, 1991); and 5.…”
Section: Western Alpsmentioning
confidence: 96%
“…CPOs of olivine in natural shear zones were studied in Josephine Peridotite in southeastern Oregon, US (Warren et al, 2008;Skemer et al, 2010;Hansen and Warren, 2015), in the Red Hills, New Zealand (Webber et al, 2008), in the Hilti massif, Semail ophiolite, Oman (Linckens et al, 2011), in an extensional shear zone in the mantle, Lanzo massif, Italy (Kaczmarek and Tommasi, 2011), in an oblique-slip low-angle shear zone in the Beni Bousera peridotite (Rif Belt, Morocco) (Frets et al, 2014), in the mylonitic peridotites in the Ronda massif, Southern Spain (Precigout et al, 2017), and in Yugu peridotites in South Korea (Fig. 7) (Park and Jung, 2017).…”
Section: Cpos Of Olivine In Natural Shear Zonesmentioning
confidence: 99%
“…In addition, one of the important minerals in the middle and lower crust is amphibole, which is also elastically anisotropic (Aleksandrov and Ryzhova, 1961a;Siegesmund et al, 1989;Weiss et al, 1999;Kaczmarek and Tommasi, 2011;Lloyd et al, 2011;Ji et al, 2013;Ko and Jung, 2015;Brown and Abramson, 2016;Almqvist and Mainprice, 2017). A recent experimental study under simple shear at high pressure and temperature showed that the CPO of amphibole (hornblende) might cause large seismic anisotropy (Ko and Jung, 2015).…”
Section: Introductionmentioning
confidence: 99%